2018
DOI: 10.1249/jsr.0000000000000545
|View full text |Cite
|
Sign up to set email alerts
|

Care of the Transgender Athlete

Abstract: Transgender individuals identify as a gender different than their sex designated at birth. Transgender athletes, as the name implies, are transgender individuals who participate in sports/athletics. By reviewing the literature relevant to transgender athletes and adding commentary on important considerations, this article acts as a primer for the sports medicine clinician on the care of transgender athletes. We cover terminology, epidemiology, policy, and relevant medical considerations. Literature relevant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…Significant issues related to exclusion and participation are likely to emerge from a general lack of awareness and understanding of the nuances of transgender bodies in sport (Caudwell, 2014). Sport, in being organized by the traditional gender binary, fails to recognize the multiplicity and complexity of gender and perpetuates the exclusion of transgender athletes (Caudwell, 2014;Dubon et al, 2018;Symons et al, 2010;Travers & Deri, 2011). Change rooms or locker rooms have long been regarded as especially problematic and traumatic for transgender people (e.g., Sykes, 2009Sykes, , 2011 with growing mobilization for the advent of gender-neutral or universal locker rooms (e.g., Beemyn et al, 2005).…”
Section: Transgender Athletesmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant issues related to exclusion and participation are likely to emerge from a general lack of awareness and understanding of the nuances of transgender bodies in sport (Caudwell, 2014). Sport, in being organized by the traditional gender binary, fails to recognize the multiplicity and complexity of gender and perpetuates the exclusion of transgender athletes (Caudwell, 2014;Dubon et al, 2018;Symons et al, 2010;Travers & Deri, 2011). Change rooms or locker rooms have long been regarded as especially problematic and traumatic for transgender people (e.g., Sykes, 2009Sykes, , 2011 with growing mobilization for the advent of gender-neutral or universal locker rooms (e.g., Beemyn et al, 2005).…”
Section: Transgender Athletesmentioning
confidence: 99%
“…Change rooms or locker rooms have long been regarded as especially problematic and traumatic for transgender people (e.g., Sykes, 2009Sykes, , 2011 with growing mobilization for the advent of gender-neutral or universal locker rooms (e.g., Beemyn et al, 2005). In addition to the (re)organization of sporting policies, practices, and spaces, the role of coaches has been identified as being integral to establishing and maintaining trans-inclusive sporting environments (e.g., Birch-Jones, 2017;CCES, 2012;Dubon et al, 2018;Lucas-Carr & Krane, 2011). Subsequently, a variety of sport-affiliated organizations have created workshops and presentations designed to educate coaches, athletes, and sports staff on how sexuality and gender-based prejudices are perpetuated through sport (e.g., Canadian Association for the Advancement of Women and Sport and Physical Activity, 2018; Egale Canada Human Rights Trust, 2019).…”
Section: Transgender Athletesmentioning
confidence: 99%
“…16 However, some transgender athletes feel dissonance due to the unfair advantage accorded by testosterone. 17 Moreover, they may also be negatively impacted by their teams, such as through discrimination or harassment. 17 In this regard, athletic professionals, including 6 / 31 sports team staff, can play a significant role in promoting an inclusive and supportive environment.…”
Section: Introductionmentioning
confidence: 99%
“…17 Moreover, they may also be negatively impacted by their teams, such as through discrimination or harassment. 17 In this regard, athletic professionals, including 6 / 31 sports team staff, can play a significant role in promoting an inclusive and supportive environment. 13,16 Studies have shown that medical providers and athletic trainers 13 may lack knowledge of transgender issues in athletes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation